2006
DOI: 10.1089/fpd.2006.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Prevalence ofEscherichia coliO157,Salmonella, Listeria,and Bacteriophage InfectingE. coliO157:H7 in Feedlot Cattle in the Southern Plains Region of the United States

Abstract: Escherichia coli O157:H7, Salmonella, and Listeria are foodborne pathogens of critical importance that often colonize cattle. E. coli O157:H7 can be specifically killed by lytic bacteriophage, and lytic bacteriophage treatment has been suggested as a pre-harvest intervention strategy to reduce foodborne pathogens in cattle. To date, no systematic approach to determine the incidence of E. coli O157:H7-infecting lytic bacteriophage has been published. Therefore, the current study was designed to determine (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…The overall prevalences of phages from fecal samples of SS (8.3%) and LS (20.9%) were similar to the range (11.7 to 23.3%) reported previously (36). Phages may fluctuate in concert with populations of E. coli O157:H7 (23), and low populations of E. coli O157:H7 may have been due to the presence of O157-specific phages in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The overall prevalences of phages from fecal samples of SS (8.3%) and LS (20.9%) were similar to the range (11.7 to 23.3%) reported previously (36). Phages may fluctuate in concert with populations of E. coli O157:H7 (23), and low populations of E. coli O157:H7 may have been due to the presence of O157-specific phages in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Aliquots (450 l) of filtrate from pats and rectal fecal material, centrifuged slurry filtrate, or concentrated trough water were incubated for 1 h at 37°C with 50 l E. coli O157:H7 R508 in early log phase (optical density at 600 nm ϳ 0.2 to 0.3). The filtrate-bacterium mixtures (20 l) were then spotted in quadruplicate onto modified nutrient agar containing 8.5 g/liter NaCl, 1 mM CaCl 2, 1 mM FeCl 3 , and 4 mM MgSO 4 . The presence or absence of plaques was recorded after 18 to 24 h incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…For enrichment, ϳ1 ml of filtrate or trough concentrate was added to a 5-ml early-log-phase (optical density at 600 nm ϳ 0.2 to 0.3) culture of E. coli O157:H7 R508 in tryptic soy broth with 10 mM MgSO 4 and further incubated at 37°C in a rotary shaker (150 rpm) for 18 to 20 h. A 1.8-ml subsample of the overnight culture was then centrifuged at 11,000 ϫ g for 10 min and filtered through a 0.22-m syringe filter. The filtrates were then tested by the soft-agar overlay plaque assay described by Sambrook and Russell (19), using E. coli O157:H7 R508 as the host.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet can also influence the physiological condition of the gut and was reported to affect the colonization of E. coli O157:H7 and Listeria spp., which altered their shedding Buchko et al, 2000;Jacob et al, 2008a). Callaway et al (2006) reported that E. coli O157 (5-20% of samples) and Listeria spp. (0-10% of samples) were isolated in fecal samples from 4 feedlots within 45 min of morning feeding.…”
Section: Introductionmentioning
confidence: 99%